Hubungan Kekerabatan Fenetik Famili Apocynaceae Berdasarkan Karakter Morfologi dan Anatomi - Ahsanul Buduri Agustiar; Dewi Masyitoh; Irda Dwi Fibriana; Adesilvi Saisatul Khumairoh; Kurnia Alfi Rianti; Norma Fitriani; Muhammad Harissuddin; Hafidha Asni Akmalia (Universitas Muhammadiyah Prof. Dr. Hamka, 2020)
Background: Biodiversity in Indonesia is so diverse, including in Apocynaceae plants that is why it is important to study the kinship relationship to find out the kinship of Apocynaceae. The purpose of this study was to determine phenetic kinship through morphological and anatomical evidence from four members of the Apocynaceae family. Methods: The method used in this research is descriptive qualitative and quantitative method. The samples in this study were four species of Apocynaceae family members, including Adenium obesum, Plumeria rubra, Catharanthus roseus, and Allamanda cathartica. The indicators used were the morphological traits of stems, leaves, and flowers and the anatomical trait of stomata. Results: The result showed that the phenetic kinship of the four species of the Apocynaceae family member namely Alamanda cathartica had a distant kinship relationship with the other species with a similarity value of 31%. Conclusions: Thus, the familial relationship between species in the Apocynaceae family in terms of morphological and anatomical characters that have a close relationship with Plumeria rubra and Adenium obesum with a similarity value of 44% and the most distant Alamanda cathartica with a similarity value of 31%.